“To My Fellow Sisters” : Discourse on the Washroom Walls - Gadsby, Jane (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1996)
This report on an investigation of washroom graffiti at York University maintains that significant differences are to be found in the latrinalia of men and women. The graffiti are broken down by subject matter and linguistic register as well as by gender of writers. The author found that women’s graffiti tended to be more dialogic in nature and, she asserts, were more expressive of solidarity and mutual aid. She relates her findings to the broader context of culturally shaped notions of gender identity.